The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2147/opth.s14332
|View full text |Cite
|
Sign up to set email alerts
|

Axial eye length measurements pre- and post- laser-assisted in situ keratomileusis using the IOL Master: a pilot study

Abstract: PurposeA preliminary study in order to test the accuracy of the IOL Master in detecting axial eye length changes after laser-assisted in situ keratomileusis and to correlate the findings with the theoretical ablation depth.MethodsPre-and postoperative axial eye length measurements were performed in 10 consecutive eyes that underwent laser-assisted in situ keratomileusis with the Alcon Ladar Vision excimer laser to treat myopic refractive errors ranging from −2.50 to −8.00 diopters of spherical equivalent (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The search found 28 articles and 9 of them were retained as relevant articles ( Table 1 ). In particular: one paper was related to changes occurred after Radial Keratotomy (RK) ( 23 ), six papers after Photorefractive Keratectomy/Laser-Assisted Sub-Epithelial Keratectomy (PRK/LASEK) ( 7 , 24 28 ), and two papers after Laser-Assisted in situ Keratomileusis (LASIK) ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search found 28 articles and 9 of them were retained as relevant articles ( Table 1 ). In particular: one paper was related to changes occurred after Radial Keratotomy (RK) ( 23 ), six papers after Photorefractive Keratectomy/Laser-Assisted Sub-Epithelial Keratectomy (PRK/LASEK) ( 7 , 24 28 ), and two papers after Laser-Assisted in situ Keratomileusis (LASIK) ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a 2010 study, Chalkiadakis et al ( 29 ) performed AL measurements using IOLMaster pre and post LASIK to treat 10 eyes of 5 patients with myopic refractive errors ranging from −2.50 to −8.00 spherical equivalent diopters (mean: −5.23 ± 1.30 D). A statistically significant AL decrease was found ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in ablation depth of 1micron led to a decrease in axial length of 0.00118 ± 0.00005mm. A study by Chalkiadakis et al 31 stated that the axial length changes between theoretical and practical measurements were not correlating. They could not conclude any correlation between ablation depth and change in axial length.…”
Section: Discussionmentioning
confidence: 98%
“…diopters of SE (mean:-5.23 ± 1.30), preoperative and postoperative AL measurements using IOL Master showed a change in AL from mean 25.80 ± 1.01 mm to 25.68 ± 0.93 mm ,one month after surgery ,showing a decrease in AL that did not have a good correlation with theoretical ablation depth. 13 In Rajan et al Study to evaluate long term refractive stability for myopic PRK, they reported stability of refraction at 12 years ,with no signi cant change in mean SE between 1, 6, and 12 years and no late regression in long term. 14 Other studies of myopic refractive surgeries have also shown mild regression in long term.…”
Section: Discussionmentioning
confidence: 99%